A Comparison of Tools and Methods for Estimating Groundwater‐Surface Water Exchange. Issue 1 (20th January 2020) - Cremeans, M.M.; Devlin, J.F.; Osorno, T.C.; McKnight, U.S.; Bjerg, P.L.
Abstract: A comparison of tools for measuring discharge rates in a sandy streambed was conducted along a transect near the north bank of the Grindsted Å (stream), Denmark. Four tools were evaluated at six locations spaced 3 m apart in the stream: mini‐piezometers, streambed point velocity probes (SBPVPs), temperature profilers, and seepage meters. Comparison of the methods showed that all identified a similar trend of low to high groundwater discharges moving westward along the transect. Furthermore, it was found that the differences between discharges estimated from Darcy calculations (using the mini‐pizometers), and SBPVPs were not statistically different from zero, at the 90% confidence level. Seepage meter estimates were consistently lower than those of the other two methods, but compared more reasonably with the application of a correction factor of 1.7, taken from the literature. In contrast, discharges estimated from temperature profiling (to a depth of 40 cm) were found to be about an order of magnitude less than those determined with the other methods, possibly due to interferences from horizontal hyporheic flow. Where the various methods produced statistically different discharge estimations at the same location, it is hypothesized that the differences arose from method‐specific sources of bias, including installation depths. On the basis of this work, practitioners interested in measuring flow across the groundwater‐surface water interface achieve the least variability with seepage meters and the SBPVP. However the accuracy of the seepage meter depended on a calibrated correction factor while that of the SBPVP did not.